Flexing and the Ethics of Wealth in the Qur'an: A Maqasidi Interpretation of Qarun's Story in Q.S. Al-Qashas, Verse 76-82 - Hijjiyah , Syivaul Hikmatul; Maghfiratuzzahroh (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to explore the phenomenon of flaunting wealth, commonly referred to as